Dynamics, Costs, and Survival of Minorities: Optimal Language Policies for Increasing the Vitality of Minority Languages - Wickström, Bengt‐Arne (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
It is assumed that language policy can influence the language in which parents choose to raise their children. A basic model of language transmission in the family is outlined and the effect of different policies on the vitality of a minority language is analyzed. It is argued that the habitation patterns and numerical strength of the minority have a strong influence on the cost effectiveness of various policy measures. It is shown that by classifying language policies into four distinct categories we can assign different policies to different minorities in a cost-effective manner, based on the size of the jurisdiction where the minority lives and its numerical strength within it. We provide a general intuitive discussion and a specific example to support the general analysis.